Perceptions and Practices of Physical Activity Among Colombian Overweight/Obese Schoolchildren - Patricia Olaya-Contreras; Diana-Carolina Ocampo; Eva Ladekjær Larsen (SAGE Publishing, 2016)
The purpose of this study was to explore the contexts that shape obese children's engagement in physical activity (PA) focusing on children's perceptions. The qualitative design consisted of non-participant observations, and unstructured and semi-structured focus group and individual interviews. Data were analyzed by use of conventional content analysis. Participants were overweight/obese children from a public school in Colombia. The findings show that the main context where PA took place was during physical education (PE) classes at school and in the children's neighborhoods. The participants perceived the PE classes to be too competitive and demotivating. PA taking place outside school was associated with fun, but occurred only on an infrequent basis and was challenged by living in insecure neighborhoods. Adapting a health promotion approach that emphasizes participation and social environments might motivate obese children to become physically active at school as well as during leisure time.